UNDERSTANDING SUCCESS IN OLD AGE FOR THE MILLENNIAL GENERATION: PHENOMENOLOGICAL METHOD - Jaelani, Muhammad Noer Qamaruddin; Panggayudi, Dwi Songgo; Maretasari, Rina; Mocklas, Mochammad (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study explores the meaning of success in old age as perceived by millennial workers at PT. PLN (Persero) ULP Taman through a phenomenological approach. The research examines their experiences, perspectives, and challenges in preparing for retirement. Method: The study employs a phenomenological approach to understand how millennial workers define and prepare for success in old age. Results: Key findings reveal that millennial workers define success in old age as a combination of good health, financial stability, and family happiness. The study highlights the importance of meticulous planning in areas such as financial management, skill development, and work-life balance. Spiritual values also emerged as critical components in shaping perceptions of future success. Novelty: The novelty of this study lies in its focus on the interplay between personal, professional, and spiritual dimensions in constructing the meaning of successful aging among millennial workers. Insights from this research provide valuable recommendations for organizations to design development programs supporting employees' long-term well-being.